Küçük Adaları Geliştirme Birliği (sıds) Kriterleri Bağlamında Yapı Malzemesi Alkerin Kuzey Kıbrısta Sürdürülebilirliği - Çebi, Demet (Fen Bilimleri Enstitüsü, 2015)
Sürdürülebilirlik küçük adalar için diğer kıta ülkelerinden daha önemlidir. Adalar birliği sürdürülebilirlik için ekoloji, ekonomi, ve enerji kullanımını dikkate almalıdır. Küçük ada ülkeleri, sürdürülebilirliği etkileyen konuları belirlemek için Küçük Adaları Geliştirme Birliğini kurdular. Küçük Adaları Geliştirme Birliği, sürdürülebilirliğin fark edilmesini sağlamak için kriterler belirlemiştir. Kriterlerden yola çıkarak, Kuzey Kıbrıs’taki konut sektörünün sürdürülebilirliği incelenmektedir. Konutun ekoloji, ekonomi, ve enerji kullanımı üzerinde büyük etkisi vardır. Konut sektöründe gerek yapım, gerekse kullanım aşamalarında enerji kullanımı, dış ticaret açığında büyük kayıplara yol açmaktadır. Son on yılda konut ihtiyacı artışı Kuzey Kıbrıs’taki sürdürülebilirliği etkileyecektir. Bölüm birde çalışmanın amacı, araştırma metodu ve çalışmanın sınırları belirtilmektedir. Bölüm ikide Küçük Adaları Geliştirme Birliğinin kriterleri açıklanmaktadır. Ekoloji, ekonomi ve ticaret, ve enerji kriterlerin ana başlıklarıdır. Biyolojik çeşitlilik, iklim değişikliği, temiz su kaynakları, ve atık yönetimi, ekoloji altında incelenmektedir. Yenilenebilir enerji, enerjinin elde edilebilirliği, enerji ve ulaşım, enerji altında incelenmektedir. Güney Kıbrıs, Kıbrıs Cumhuriyeti olarak Küçük Adaları Geliştirme Birliğine üyedir. Kriterler Kıbrıs’ı örnek alarak değerlendirilmektedir. Kuzey Kıbrıs, birliğe üye olmamasına rağmen diğer küçük adaların sorunlarını yaşamaktadır. Güney Kıbrıs üye olduğuna göre, kriterler Kuzey Kıbrıs’ta da uygulanabilir. Kriterlerin Kuzey Kıbrıs’ta ki eksikliği bu bölümde son olarak incelenmektedir. Bölüm üçte Kuzey Kıbrıs’ta ki yapı malzemeleri ve konut ihtiyacı incelenmektedir. İklimsel, topoğrafik, coğrafik özellikler ve kırsal kerpiç evin özellikleri anlatılmaktadır. Yapı malzemesi olarak toprak, stabilize edilmiş kerpiç çeşitleri ve alker bu bölümde incelenmektedir. Bölüm dörtte yapı malzemesi alker, Küçük Adaları Geliştirme Birliğinin kriterleri bağlamında incelenmektedir. Amaç, alkerin ekolojiye ekonomiye ve enerji talebine katkısı anlatılmaktadır. Son olarak sürdürülebilirlik kavramı ve alkerin sürdürülebilirliği anlatılmaktadır. Bölüm beş tezin sonuç kısmıdır. Yapı malzemesi alkerin kullanımıyla dış ticaret açığının dengelenmesi, enerji kullanımında %35 azalma, ve doğaya daha az atık bırakılması hedeflenmektedir.

Sustainability in islands is more important than other continent countries. Island states have to consider the ecology, economy and energy consumption for sustainability. The island countries established “Small Island Development States” network to determine subjects affecting sustainability. Small Island Development States influenced the sustainability criteria, in order to make contribution to the awareness. Going out of these criteria, it will investigate the sustainability of Northern Cyprus in case of housing sector. Housing has a big impact on ecology, economy and energy consumption. The energy used in housing both during the construction and lifecycle causes great value loss in foreign trade balance. Housing demand rises in the last decay, which will affect he sustainability of Northern Cyprus. In chapter one, the aim of this study, research methods and limitations are explained. In chapter two, criteria’s of Small Island Development States are explained. Ecology, trade and economy, and energy are the main topics of criteria’s. Ecology is investigated as biodiversity, climate change, freshwater resources, and waste management. Energy is investigated as accessibility of energy, energy efficiency, renewable energy, energy and transportation. South Cyprus as Cyprus Republic is a member of Small Islands Developments States. The criteria are examined in Cyprus. North Cyprus is not a member but has same problems with other small islands. Since the south part is a member, the criteria should be applied in North part as well. The lack of criteria in North Cyprus is examined. In chapter three, housing needs and construction materials in North Cyprus is explained. Climatic conditions, topography, and geography and rural earth house of Cyprus is examined. Earthen as a construction material, traditional mud-brick, stabilized earth types and alker are investigated in this chapter. In chapter four, investigation of alker according to Small Island Development States criteria’s are examined. Using alker in North Cyprus and its contribution to ecology economy and to the energy demand are the core of this chapter. Sustainability and sustainability of construction material alker are examined at the last part of this chapter. Chapter five is the conclusion part of the thesis. Foreign trade will be balanced by using construction material alker, 35% less energy consumption, and less pollutant will be leaved to the nature will be achieved by using alker.
Sustainability Of Construction Material Alker In North Cyprus At The Context Of Small Island Development States Criteria
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2005
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2005
Keywords: Küçük Adaları Geliştirme Birliği; Ekoloji; Ekonomi; Ticaret; Enerji; Sürdürülebilirlik; Kuzey Kıbrıs; Güney Kıbrıs; Kerpiç; Alker; Small Island Development States; Ecology; Economy; Trade; Energy; Sustainability; North Cyprus; South Cyprus; Earth; Alker